Analysis of Waste Management Policy by the Dumai City Environmental Agency: Literature Review - Puja, Rahmadini; Sumiati, Sumiati; Erinaldi, Erinaldi (Rechtsvinding, 2025)
Waste management has become a strategic environmental issue for Dumai City, an industrial area with a high and continuously increasing volume of daily waste, thereby requiring policies capable of responding to environmental and operational challenges in a sustainable manner. This study aims to analyze the waste management policy implemented by the Dumai City Environmental Agency using Dunn’s six policy evaluation indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The research applies a literature review method by examining local regulations, official government reports, news publications, and relevant previous studies. The findings show that Dumai’s waste management policy is supported by a strong regulatory framework, including regional regulations and mayoral decrees, and is strengthened through various programs such as waste banks, the restructuring of the Mekar Sari landfill, expansion of the sanitation fleet, and collaboration with the Ministry of Environment and Forestry. However, policy implementation still faces several obstacles, including the high waste generation reaching 180 tons per day, limited landfill capacity, inadequate processing facilities, low public awareness of waste sorting, and uneven distribution of waste management services. These issues indicate that although the policy direction is appropriate and responsive to community needs, its effectiveness and adequacy require significant improvement through increased infrastructure capacity, additional processing technology, expansion of 3R programs, and intensified public education. This study underscores the need for a more comprehensive and sustainable strategy that integrates government efforts with active community participation to enhance the overall effectiveness of waste management in Dumai City.